"I wanted to communicate my feelings freely": a descriptive study of creative responses to enhance reflection in palliative medicine education. Issue 1 (December 2015) - McBain, Lynn; Donnelly, Sinéad; Hilder, Jo; O'Leary, Clare; McKinlay, Eileen
Abstract Background The recent growth of arts and humanities in medical education shows recognition that these disciplines can facilitate a breadth of thinking and result in personal and professional growth. However creative work can be a challenge to incorporate into a busy curriculum. Offering the option of creative media as a way of reflecting is an example of how this can occur. This study aimed to examine the medical student response to being given this option to explore a visit to a patient in a hospice. Methods This was a mainly qualitative study. In the 2012 academic programme, the class of 86 students were given the option of using a creative medium to explore their responses to both the visit and their developing communication skills. Students were required to write an accompanying commentary if submitting the creative work option. Sixty-four percent of the class chose a creative medium e.g. poetry, visual art, narrative prose, music. These students were asked to take part in research including completing a short on-line survey and consenting for their creative work and commentaries to be further examined. The creative works were categorised by genre and the commentaries analysed using inductive thematic analysis. Results Seventeen students completed the on-line survey and fifteen consented to their work being used for this research. Thematic analysis of the student commentaries revealed the following themes: effectiveness for expressing emotion or ideas that are difficult to articulate; engaging and energising quality of the task; time for reflection; flexibility for individual learning styles and therapeutic value. Conclusions Teaching the art of communicating at end-of-life is challenging especially when it involves patients, and teachers want to ensure students gain as much as possible from the experience. Offering the option to use creative media means that students can choose a medium for reflection that best suits them as individuals and that can enable them to benefit as much as possible from their experience.